Geotechnical investigations of lead-silver ore processing residues at the Auzelles site, Auvergne (France) - Diaka Sidibé; Mamadou Diallo; Ahmed Amara Konaté; Muhammad Zaheer (AIMS Geosciences)
Mining operations generate a significant quantity of mining waste in the form of sterile rocks and processing residues. These mining wastes are typically placed on the surface and can cause geotechnical and geochemical disturbances, as well as contaminants in surface water (through runoff) and groundwater (through infiltration), thus posing environmental risks. This article aimed to characterize the geotechnical properties of lead-silver ore processing residues at the Auzelles site in order to assess their stability and propose recommendations for their management and rehabilitation. The adopted methodology included in situ tests (such as density measurement and permeability) and laboratory analyses (grain size distribution, moisture content, methylene blue test, direct shear test, and standard Proctor test). The results showed a wet density of 1.63 g/cm3 for the residues compared with 1.65 g/cm3 for the waste rock, as well as a permeability of the residues measured at 5.5 × 10-5 m/s, indicating significant drainage capacity. Laboratory analyses revealed that the samples were primarily composed of very silty sands and gravel, classified as B5 according to the Guide to Road Settlements. The cohesion of the residues was found to be zero, while the internal friction angle varied between 28° for the residues and 30° for the foundation soils. These geomechanical properties, particularly density, lack of cohesion, and friction angle values, raise concerns about the long-term stability of the residues. Due to their high permeability and lack of cohesion, the residues are susceptible to mass movement and erosion, which may exacerbate contamination risks. Therefore, it is essential to integrate these parameters into any potential residue stability analysis. Proactive management, based on these results, requires the implementation of appropriate rehabilitation techniques, such as drainage optimization and incorporation of vegetation covers, to minimize environmental impacts and ensure the long-term sustainability of mining waste structures.